Director's Review: MARA Institute of Technology: July 1973 to June 1974/ MARA Institute of Technology - ITM, Institut Teknologi MARA (MARA Institute of Technology, 1974)
Contains director's remarks, academic programmes, faculty, students, administration, finance and physical plant.